2018
DOI: 10.4194/1303-2712-v18_3_11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Nucleotide sequences of the Cytochrome oxidase subunit I gene and Cytochrome b were analyzed for Ö10 processed fish products collected from supermarkets in Hanoi, Viet Nam. The similarity between our results and published data from the NCBI and BOLD was compared to identify species. This molecular analysis showed that the common names of only 4 of these products matched with their corresponding scientific names. The other six were mislabeled with an important mislabeling from P. hypophthalmus into P. boucourti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, 15% of samples coming from Italian markets were mislabelled, thus confirming the existence of commercial fraud at an international level. In similar research, Ha et al [ 116 ] carried out an analysis of 10 processed fillets collected from department stores in Hanoi (Vietnam). Only four of these products matched common and corresponding scientific names after the appropriate barcoding evaluation.…”
Section: Dna Barcode Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 15% of samples coming from Italian markets were mislabelled, thus confirming the existence of commercial fraud at an international level. In similar research, Ha et al [ 116 ] carried out an analysis of 10 processed fillets collected from department stores in Hanoi (Vietnam). Only four of these products matched common and corresponding scientific names after the appropriate barcoding evaluation.…”
Section: Dna Barcode Regionsmentioning
confidence: 99%
“…The other six samples exhibited inappropriate labelling, switching from P. hypophthalmus into P. boucourti . Although no real commercial fraud was found in these products, the correct scientific names of fish species should always be considered for elaborated products as they are publicly available in supermarkets where people have no specific consciousness of this problem [ 116 ]. Meanwhile, Cutarelli et al [ 117 ] analysed 60 samples of canned fish belonging to three genera and five species collected by Italian Health authorities: PIF (Border Inspection Posts), NAS (Anti-Sophistication Police) and ASL (Local Health Authority).…”
Section: Dna Barcode Regionsmentioning
confidence: 99%
“…Previous studies reported that a 3% genetic divergence is widely used in animal barcoding as a species border (Hubert et al 2012;Ko et al 2013;Mohammed et al 2021;Riani et al 2021). Several studies have also explored various thresholds as species border during molecular identification from less than 1% to 5% (Cote et al 2013;Aguilar et al 2017: Ha et al 2019Abdalwahhab et al 2020). Previous studies stated that genetic divergence in well-identified species ranges from 0.00% to 9.31% (Brando et al 2016;Landschoff and Gouws 2018;Lipinskaya et al 2018;Rahman et al 2019;Rossel and Arbizu 2019;Rahman et al 2020).…”
Section: Taxonomic Status Of Crustacean Larvaementioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) is a major target in DNA barcoding because: (1) it generally lacks large noncoding regions; (2) it is abundant and relatively easy to analyze; (3) it does not undergo genetic rearrangements such as recombination; (4) sequence ambiguities resulting from heterozygous genotypes can be avoided, and (5) regions with low intraspecies and high interspecies variation are already identified. Although several mtDNA regions such as 16S rRNA (Itoi et al, 2005; Kochzius et al, 2008) and cytochrome b (Ha et al, 2018; Itoi et al, 2020; Pepe et al, 2005) have been used for DNA barcoding, the 5’ region of cytochrome c oxidase subunit I (COI) has become a dominant region for identifying fish mislabeling (Di Pinto et al, 2013; Panprommin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%